The Midrashic imagination : Jewish exegesis, thought, and history - Fishbane, Michael, 1943- (State University of New York Press, 1993)
Annotation. Examines the broad range of Jewish interpretation from antiquity through the medieval and renaissance periods, focusing primarily on Midrash and midrashic creativity that includes the entire range of nonlegal interpretations of the Bible. Explores Midrash, considered as a literary and cultural form, from various perspectives, including mythmaking and parables. Paper edition (unseen), $16.95. Annotation copyright by Book News, Inc., Portland, OR.
Keywords: Midrash -- History and criticism.; Bible. -- Old Testament -- History -- Criticism, interpretation, etc., Jewish.; Bible. -- Old Testament; RELIGION -- Judaism -- Sacred Writings.; Midrash; Judaismo.; Criticism, interpretation, etc.; History